Use of Innovations and Foreign Experiences in Education of Students on Life Safety - Shermatova Yakut Sabirovna (Genius Journals, 2022)
The article provides theoretical information and analysis of innovations and best foreign practices used in teaching students about life safety. There are also innovations, interactive methods, case studies, cases, assignments used in practical training
Keywords: Life; safety of life activities; emergencies